REGARDING THE WORK DONE IN THE AREA OF OVERSEEING THE ENFORCEMENT OF LEGISLATION RELATED TO THE PROTECTION OF ATMOSPHERIC AIR (American Journal of Interdisciplinary Research and Development, 2024)
The article describes the problem of air pollution in cities, including the types of atmospheric pollution and methods to minimize their negative impacts.